Penerapan Metode SAW untuk Mengurangi Subjektivitas dalam Menentukan Kelayakan Penerima PKH - Rochanah Rochanah; Nuryanto Nuryanto; Mukhtar hanafi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study aims to determine the priority scale for families eligible to receive benefits from the Family Hope Program (PKH) using the Simple Additive Weighting (SAW) method. The primary issue addressed is the limited allocation of assistance, which necessitates an objective and transparent selection process to ensure that aid reaches the families most in need. This research aims to provide a decision support system-based solution to assist in the selection process.The research employs the SAW approach, which involves several key steps: collecting data on prospective beneficiary families, normalizing the data to standardize the criteria scale, assigning weights to each criterion according to its importance, and calculating the final scores to rank each family. The criteria used include the number of family members, the presence of young children, the educational level of family members, disability status, elderly status, and pregnancy, with weights determined based on policy. The results indicate that the SAW method effectively identifies the families most in need based on objectively calculated total scores. From the total data tested, 75% of families were categorized as